2018
DOI: 10.4155/fmc-2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

Search of Vasopressin Analogs with Antiproliferative Activity on Small-Cell Lung Cancer: Drug Design Based on Two Different Approaches

Abstract: Combination of these strategies could provide the basis for future studies for the development of improved compounds with potential therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…In line with these findings, complete reversal of in vitro [V 4 Q 5 ]dDAVP activity after AVPR2 chemical blockade was also reported by our group in highly aggressive breast cancer cells [15]. Moreover, we recently showed that after siRNA-mediated knockdown of AVPR2 expression in human lung carcinoma cells, [V 4 Q 5 ]dDAVP antiproliferative effects were significantly attenuated, confirming AVPR2-dependency of [V 4 Q 5 ]dDAVP cytostatic action in malignant cells [5,27]. In this experimental setting, the development of a CRC cell model with AVPR2 gene knockout or knockdown is highly interesting, and should be pursued with the aim of corroborating previously described findings.…”
Section: Discussionsupporting
confidence: 75%
“…In line with these findings, complete reversal of in vitro [V 4 Q 5 ]dDAVP activity after AVPR2 chemical blockade was also reported by our group in highly aggressive breast cancer cells [15]. Moreover, we recently showed that after siRNA-mediated knockdown of AVPR2 expression in human lung carcinoma cells, [V 4 Q 5 ]dDAVP antiproliferative effects were significantly attenuated, confirming AVPR2-dependency of [V 4 Q 5 ]dDAVP cytostatic action in malignant cells [5,27]. In this experimental setting, the development of a CRC cell model with AVPR2 gene knockout or knockdown is highly interesting, and should be pursued with the aim of corroborating previously described findings.…”
Section: Discussionsupporting
confidence: 75%
“…Using the AVPR2-expressing MG-63 model, we showed that, in accordance with previously reported preclinical studies (14,(16)(17)(18)(23)(24)(25), in vitro dDAVP treatment reduced osteosarcoma cell growth and chemotaxis, and cytostatic activity was related to increased cAMP intracellular levels upon AVPR2 stimulation. Furthermore, inhibition of cAMP-degrading phosphodiesterases by addition of rolipram enhanced the antiproliferative effects of dDAVP in osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 89%
“…dDAVP has been used as a blood-saving agent for nearly 50 years in patients with bleeding disorders or undergoing complex surgeries characterized by large blood loss (11). This compound is a 1st generation synthetic analog of the vasopressin hormone (AVP) and acts as a selective agonist for the vasopressin membrane receptor type 2 (AVPR2) expressed in microvascular endothelium (12) and several transformed tissues, including breast (13)(14)(15), prostate (16), lung (17) and colorectal cancer (18,19). Agonistic stimulation of vascular AVPR2 is associated with a cyclic adenosine monophosphate (cAMP)-mediated acute release of several hemostatic factors into the bloodstream, including factor VIII, tissue-type plasminogen activator and von Willebrand factor (VWF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is a leading cause of cancer-associated death worldwide [1,2]. Explanation of the molecular biology and pathogenesis of lung cancer is essential for the design of a potential treatment for patients [3,4]. Non-small-cell lung carcinoma (NSCLC) is a complex process concerning interruption of cell proliferation, cell differentiation, apoptosis and various molecular mechanisms.…”
mentioning
confidence: 99%